Knowledge of Neuroscience and teaching performance at the Juan XXIII-Ica Public Pedagogical Institute - Alvaro-López, Zeida Marianela (2022)
The research was designed from the problem: What is the relationship between the level of knowledge of neuroscience and teaching performance at the Juan XXIII Institute of Public Pedagogical Higher Education in Ica?, and from the objective: to determine the relationship between the level of knowledge of neuroscience and teaching performance in the Public Pedagogical Institute John XXIII of Ica, approach quantitative, design correlational, sample  42 teachers, instrument questionnaire survey with Cronbach's alpha statistical consistency 0.814 and 0.87, validation and reliability: expert judgment test, establishing a relationship between variables and dimensions, dimensions with indicators and indicators with items, obtaining the V of Aiken 0.88 for the questionnaire knowledge of neuroscience and V of Aiken 0.904 for the teacher performance questionnaire. Result: for hypothesis testing Kolmogorov-Smirnov normality test with a significance level of 5% showed that 78% of respondents indicate a favorable level of knowledge of neuroscience, among the undecideds 16.7%. In conclusion, the existence of a significant relationship between the level of knowledge of neuroscience and the teaching performance of the Juan XXIII pedagogical institute of Ica was verified according to the statistical test X2 = 47,967 > X2 = 9,488 at a level less than 5% of standard significance (P < 0.05).